Global equatorial plasma bubble occurrence during the 2015 St. Patrick's Day storm. Issue 1 (30th January 2016) - Carter, B. A.; Yizengaw, E.; Pradipta, R.; Retterer, J. M.; Groves, K.; Valladares, C.; Caton, R.; Bridgwood, C.; Norman, R.; Zhang, K.
Abstract: An analysis of the occurrence of equatorial plasma bubbles (EPBs) around the world during the 2015 St. Patrick's Day geomagnetic storm is presented. A network of 12 Global Positioning System receivers spanning from South America to Southeast Asia was used, in addition to colocated VHF receivers at three stations and four nearby ionosondes. The suppression of postsunset EPBs was observed across most longitudes over 2 days. The EPB observations were compared to calculations of the linear Rayleigh‐Taylor growth rate using coupled thermosphere‐ionosphere modeling, which successfully modeled the transition of favorable EPB growth from postsunset to postmidnight hours during the storm. The mechanisms behind the growth of postmidnight EPBs during this storm were investigated. While the latter stages of postmidnight EPB growth were found to be dominated by disturbance dynamo effects, the initial stages of postmidnight EPB growth close to local midnight were found to be controlled by the higher altitudes of the plasma (i.e., the gravity term). Modeling and observations revealed that during the storm the ionospheric plasma was redistributed to higher altitudes in the low‐latitude region, which made the plasma more susceptible to Rayleigh‐Taylor growth prior to the dominance of the disturbance dynamo in the eventual generation of postmidnight EPBs. Key Points: Global EPB occurrence analyzed throughout severe 17 March 2015 storm TIEGCM modeled observed transition of postsunset to postmidnight EPB activity Postmidnight EPBs initiated by storm time redistribution of ionospheric plasma